Geographic variability of floating kelp recovery after a marine heatwave event in the Salish Sea and adjacent open coast - Danielle C. Claar; Helen Berry; Bart Christiaen (PLoS ONE, 2025)
Floating canopy kelps, foundational species that support productive nearshore marine forests, are threatened by increasingly common and severe marine heatwaves (MHW). We tracked annual changes in kelp canopies and sea surface temperature (SST) before, during, and after the 2014–2016 MHW from the open coast of Washington State, USA into the Salish Sea. We found spatial differences in kelp canopy recovery timelines and in warming magnitude and duration. Estuarine-dominated sub-regions experienced slower recovery (up to three years) than ocean-driven areas (one year), even though all sub-regions experienced coincident declines. Mean SST of the warmest month was the most common predictor of annual canopy abundance (4 of 6 sub-regions), and the best predictor in the two exposed coast sub-regions, while anomaly magnitude and duration were the best predictors in the two innermost sub-regions. These results suggest that there may be substantive differences in kelp stressors and their interactions between estuarine- and oceanic-dominated nearshore ecosystems. However, while statistically significant, these associations were weak, emphasizing the need to understand effects of MHW on canopy kelp in the context of multiple interacting drivers.